Modernized Method of Averaged Characteristics for Problem Solving of Multiharmonic Resonant Interactions in Devices of High-Current Electronics - V.V. Kulish; A.V. Lysenko; G.A. Oleksiienko; G.V. Bychenko; O.A. Koloskova (Журнал нано- та електронної фізики)
We modernize the method of averaged characteristics in the part of constructing scheme of asymptotic integration of nonlinear differential equation systems, taking into account the features of multiharmonic resonant interactions in devices high-current electronics. The schemes of asymptotic integration, which combines procedures of the straight and inverse transformation, have been constructed. We consider both the case of a fast phase, and the case of many fast phases.